Characteristics of carcass and meat of heifers finished on pasture amended with different supplement frequency and soybean oil source - Santana, Márcia C.A. [UNESP]; Messana, Juliana D. [UNESP]; Fiorentini, Giovani [UNESP]; Lage, Josiane F. [UNESP]; Dian, Paulo H.M. [UNESP]; Canesin, Roberta C. [UNESP]; Reis, Ricardo A. [UNESP]; Berchielli, Telma T. [UNESP] (Canadian Science Publishing, 2017)
Our objective was to investigate the effects of supplements with soybean oil source, administered either daily or three times per week, on meat quality and carcass characteristics of heifers finished on pasture. Forty-two crossbred heifers aged 17 ± 3 mo with an initial mean body weight (BW) of 297.1 ± 13.5 kg were selected for pasture finishing. The animals were randomly assigned to six treatments. Each treatment consisted of two feeding frequencies, daily (DAI; seven times per week, supplemented at 0.75% BW) or alternating (MWF; three times per week, on Monday, Wednesday, and Friday, supplemented at 1.75% BW on each day), and three different soybean oil sources: soybean oil (SO), rumen-protected fat (RPF), and whole soybean (WS). There was no interaction (P > 0.05) between the feeding frequencies and soybean oil source on meat quality and carcass characteristics. Supplements with WS resulted in a greater C18:0 concentration in the longissimus muscle compared with those with SO or RPF (P = 0.02). Supplements with SO increased the rumenic acid deposition, the total monounsaturated fatty acids, and the monounsaturated:saturated fatty acids ratio (P < 0.05). We conclude that reduction in the supplementation frequency does not alter the carcass and meat quality traits.
Keywords: Brachiaria brizantha; Conjugated linoleic acid; Protected fat; Soybean oil; Supplementation